Male morphotypes of the freshwater prawn Macrobrachium brasiliense (Decapoda: Caridea: Palaemonidae) - Nogueira, Caio Santos [UNESP]; Pantaleão, João Alberto Farinelli [UNESP]; Almeida, Ariádine Cristine; Costa, Rogerio Caetano [UNESP] (Wiley, 2020)
Some decapod species have intraspecific morphological variations that result in distinct adult morphotypes that influence the population structure, social dominance, and reproduction of the population. Here we investigated whether this differentiation into morphotypes occurs in adult males of Macrobrachium brasiliense, through the analysis of relative growth and morphology. Specimens were collected in the region of Uberlândia, Minas Gerais state, southeastern Brazil. Seven dimensions of each male were measured: carapace length (CL), ischium length, merus length, carpus length, propodus length, dactylus length, and major cheliped length. Principal component analysis, clustering, and discriminant analyses were used to identify possible morphotypes. The analysis of relative growth was employed to estimate the growth patterns of body structures (dependent variables) in relation to the CL (independent variable). Two morphotypes were identified: Mirim, which has less developed chelipeds (23.31 ± 3.08 mm) with fewer spines, and Açu, which has larger chelipeds (41.39 ± 8.14 mm) with many well-developed spines, especially in the merus. Most morphometric relationships differed significantly (p <.01) between the two morphotypes. The chelipeds were useful characters for the identification of the morphotypes of M. brasiliense, corroborating previous descriptions of the genus. We provide a detailed description of the main macroscopic characteristics that differed between morphotypes, which will enable their identification in future studies. Our results contribute to the knowledge of the population biology of M. brasiliense and should be considered in future investigations, since the presence of these male morphotypes probably influences the reproductive biology and population ecology of the species.
Keywords: allometry; chelipeds; relative growth; social dominance; social hierarchy